Sex and the City-State: Cultural Politics and Sexual Cultures in Love and Lust in Singapore - Gwynne, NIE, Nanyang Technological University, Singapore, Joel; Whitehead, NIE, Nanyang Technological University, Singapore, Angus (Asiatic: IIUM Journal of English Language and Literature, 2011)
In this article, we explore how the erotic short story collection Love and Lust in Singapore (2010) emblematises the cultural and sexual politics of the nation-state. We argue that the anthology presents a conflicted and contradictory view of Singapore, demonstrating a movement between conservative affirmation and liberal critique of the state's political, cultural and sexual practices. While the nation-state is presented as a participant in a global capitalist culture, the majority of the stories contained in Love and Lust challenge, in one way or another, Singapore's alleged privileging of materialism and consumerism over the domestic, cultural and spiritual needs of citizen, resident and visitor. Acutely aware of the collection's problematic status as predominantly populated by expatriates, we will argue that all of the stories in Love and Lust serve to either affirm or disavow both national state rhetoric and popular ideologies of nationhood.